Pea cultivation in semiarid regions: yield, protein content, and climatic adaptability performance - Dillchneider Loza, Alexandra; Díaz-Zorita, Martín (Elsevier, 2025)
Pea crops are valuable for both human consumption and animal feed, representing a promising option for agricultural diversification in semiarid environments. This study analyzed yield and grain production variability of winter and spring pea varieties under rainfed conditions in the central semiarid Pampas region (Santa Rosa, La Pampa, Argentina) across three growing seasons (2020, 2022, and 2023). Evaluations focused on grain yield, protein content under diverse rainfed conditions representative of the central semiarid Pampas region, and to assess their production stability across years. Spring varieties, with shorter growth cycles, outperformed winter genotypes. Among the evaluated materials, three spring cultivars and one winter cultivar demonstrated higher stability, indicating a potential adaptation to this environment. Freezing events and high temperatures during critical yield formation stages reduced productivity by decreasing grain number, whereas favorable conditions during grain filling promoted heavier grains and increased yield. Yellow cotyledon varieties achieved higher yields than green cotyledon varieties. Grain protein concentrations reached expected values and were positively associated with rainfall during the grain development stage. Overall, pea cultivation represents a valuable alternative for diversifying cropping systems in semiarid regions, although variability among cultivars and seasons highlights limitations in their adaptation to challenging climatic conditions.